IMPROVEMENT OF THERMAL TREATMENT TO ENHANCE BIOLOGICAL RESISTANCE OF FERMENTED BEVERAGES - Reshetnyak, Lyudmila; Vitriak, Oksana; Serenko, Anton (Proceedings of National Aviation University, 2018)
Purpose: The perfection the modes of thermal treatment for the increase of biological resistance of the fermented drinks that were got with the use of culture Medusomyces gisevii. Methods: We investigated the effect of thermal treatment in the range 55...80°C for 10-60 minutes to change the physicochemical and organoleptic characteristics of fermented beverages during storage and storage conditions of beverages in glass bottles (temperature, filling factor). Results: It is established that to increase the shelf life of the beverage in the optimal processing conditions are the temperature ranges and duration, respectively, of 63°C and 40 min to 75°C and 15 min. The optimum fill factor for drink based on the culture of Medusomyces gisevii in glass bottles is 0.90-0.96. Discussion: The stability of non-alcoholic fermented beverages obtained using Medusomyces gisevii culture, treated with pasteurization under conditions of two treatment regimes: 63°C and 40 min. and 75°C and 15 min was investigated. Taking into account the rather mild conditions of thermal treatment and achieved a bacteriostatic effect during 60 days of storage at 30°C, the 1th mode can be recommended as acceptable to the increase of biological firmness of drink. Storage of beverages at temperatures up to 12°C can stabilize the microbiological state up to 180 days. In the 2nd mode of heat treatment the stability of the beverage remained stable at a storage temperature of 30°C for 180 days, and at 12°C – not less than 210 days. The use of modes of thermal processing of beverage within the specified limits allows guaranteed shelf life of 2 to 6 months without significant reduction of organoleptic characteristics and content of biologically active substances compared to unprocessed beverage.